A NUMERICAL INVESTIGATION OF THE FLOW IN WATER JET NOZULES - Bilir, Ahmet Cagri; Dogrul, Ali; Cosgun, Taner; Yurtseven, Ahmet; Vardar, Nurten (YILDIZ TECHNICAL UNIV, 2016)
In this study, flow inside the nozzles are investigated by means of finite volume method. Firstly, some analyses are carried out in 2-D in order to compare and validate the results with the experimental ones. Later, 3-D models are created to have different nozzle geometries. 3-D analyses are made and outlet mass flow rates, velocities and reaction forces are calculated in the same inlet pressure level for different nozzle geometries. Two equation k-omega turbulence model is chosen as the turbulence model. At the end of this numerical study, the nozzle geometry with minimum reaction force and maximum mass flow rate is deteunined thanks to computational fluid dynamics (CFD) based on finite volume method (FVM).
Keywords: Nozzle; water jet; k-w turbulence model; CFD; Thermodynamics